Phacoemulsification Incision-Creation, Evaluation and Closure: A Review - Ajay Kumar Singh (Delhi Journal of Ophthalmology)
Creating an ideal incision is the foremost and the most crucial step in phacoemulsification. The most commonly used incision for phacoemulsification is sutureless clear corneal incision (CCI). The location, size and the architecture of incision are as important as the equipment to create it. Surgical equipment and techniques play a very important role in creation of an optimal incision. The location and the technique of incision continue to be perfected as the understanding of the dynamic architecture and the technology are improving. Newer tools such as femtosecond laser help to create a near-perfect incision improving the safety profile of the surgery. Likewise the adequate closure of the incision is equally important. Stromal hydration, suturing, tissue adhesives, such as cyanoacrylate, fibrin and polyethylene glycol (PEG), corneal soldering and tissue welding are some techniques for incision closure. Each has its own merits and demerits. This article reviews various published studies and literature related to the techniques of creation, evaluation and closure of phacoemulsification incision. PubMed and CrossRef (Google) search engines have been used as the primary media for literature research.